Integration of remote sensing and GIS for archaeological investigations - Maktav, D.; Crow, J.; Kolay, C.; Yegen, B.; Onoz, B.; Sunar, F.; Coskun, G.; Karadogan, H.; Cakan, M.; Akar, I.; Uysal, C.; Gucluer, D.; et al. (TAYLOR & FRANCIS LTD, 2009)
The western hinterland of the modern city of Istanbul contains some of the most remarkable monuments of ancient and medieval hydraulic engineering. Until recently fieldwork has been limited and only within the last two decades have there been serious attempts to map the complexity of the monuments and water lines. A GPS-based archaeological survey has been undertaken by the authors and has been integrated with high resolution (IKONOS) and multi-spectral spatial data giving the opportunity to view the system in its wider setting and also to identify major urban and landscape changes impacting on the long-term conservation and management of the ancient remains.
Keywords: Remote Sensing; Imaging Science & Photographic Technology